Relationship Between Work-Life Balance, Turnover Intention, and Organizational Support for Work-Life Balance:A Study in the IT Industry in Kerala - K., Jnaneswar (Prabandhan: Indian Journal of Management, 2016)
Work-life balance refers to the ability of individuals, regardless of age or gender, to combine work and household responsibilities successfully. It has emerged as a major theme during the last two decades. Turnover is a topic of wide interest in organizational research. Turnover intention is defined as an employee's intention to leave the current job and look forward to finding another job in the near future. Past research explained that intention to leave is one of the biggest predictors and an immediate sign of employees' turnover. A supportive work-life culture is defined as the shared assumptions, beliefs, and values regarding the extent to which organizations value and support the integration of work and family lives for women and men. The present study attempted to find out the relationship between work-life balance, turnover intention, and organizational support for work - life balance among the IT employees working in Kerala. The results revealed that there was a significant correlation between these three variables. The study also found that work-life balance was only moderate among IT professionals working in Kerala. The study established that there was a significant difference between male and female respondents with respect to work-life balance and organizational support for work-life balance. No significant difference was found between the married and unmarried employees for all the three variables. The study makes an important contribution to the body of literature on work-life balance and turnover intention. It is expected that the findings of the study would help the organizations in balancing the work and family life and thereby reduce employee turnover.